Organizational Support and Service Leadership in Improving Organizational Citizenship Behavior (OCB) Among Private High School Teachers in Depok City - Dian Renata; Sri Setyaningsih; Dian Wulandari (International journal of technology and education research, 2025)
This study aims to analyze the influence of organizational support and service leadership on organizational citizenship behavior (OCB) among private high school teachers in Depok City. Organizational citizenship behavior (OCB) refers to voluntary contributions made by employees that support organizational effectiveness, beyond their formal obligations. This study employs a quantitative approach with a survey design and involves 234 teachers from various private schools in Depok City. Data were collected through a questionnaire measuring organizational support, service leadership, and OCB. The data analysis technique used was multiple linear regression to test the influence of each variable on OCB. The results of the study indicate that both organizational support and service leadership have a significant influence on increasing OCB behavior. These findings provide insights for private school management to develop policies that support OCB behavior through adequate support and service-based leadership. Thus, this study confirms the importance of the role of organizational support and leadership in creating a productive and collaborative work environment in the education sector.